Axial compression behaviours of ultra-high performance concrete-filled Q690 high-strength steel tubes at low temperatures. (December 2021) - Yan, Jia-Bao; Yang, Xinyan; Luo, Yanli; Xie, Peng; Luo, Yun-Biao
Abstract: This paper proposed the UHPC-filled high-strength steel tube (UHST) for cold-region buildings/bridges. The cold-region low-temperature environment was simulated in the laboratory using a cooling chamber with LNG. Then, low-temperature compression tests were performed on 23 stub UHSTs to study their low-temperature compression behaviour. The studied parameters included four low temperatures ( T = −80, −60, −30, and 30 °C) and three width-to-thickness ratios ( C / t ratio = 48.4, 33.5, 22.0). Test results showed that the P (load) − Δ (shortening) curves exhibited a four-stage manner. The UHPC crushing occurred at the ultimate load capacity and UHPC nonlinearities contributed to the nonlinear behaviour of UHSTs. Outward buckling of HSS tube and welding fracture occurred at the recession stage. The decreasing temperature from 30 °C to −80 °C improved the compression behaviour of UHSTs. As T decreases form 30 °C to −80 °C, the ultimate compressive resistance P u (or initial stiffness K 0 ) value of UHSTs with C / t ratio of 22.0 receives the increments of 20% (24%). With the same decrease of C / t ratio, the increments of peak load capacity decreased as T decreased from 30 °C to −80 °C. This paper also developed finite element models (FEMs) and theoretical models to simulate the axial compression behaviour of UHSTs at low temperatures. Validations of simulations against 23 test results proved that both the FEM and theoretical models provided reasonable simulations on axial low-temperature compression behaviours of UHSTs. Highlights: Low temperature improves load capacity of UHPC-filled Q690 high strength steel tube (UHST). UHST with Q690 UHSS exhibits close compression behaviours at low and room temperature. FEM predicts well low-temperature compression behaviour of UHST with Q690 HSS. Developed theoretical models predict well low-temperature P- Δ curves of UHSTs.